2011
DOI: 10.1007/s10899-011-9266-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sleep Debt on Risk Perception, Risk Attraction and Betting Behavior During a Blackjack Style Gambling Task

Abstract: Gamblers often gamble while experiencing fatigue due to sleep deprivation or cumulative sleep debt. Such fatigue has been shown to make decision makers behave more riskily. The present study aimed to test the role of two cognitive processes, risk perception and risk attraction, in this effect. Two hundred and two participants played twelve hands of a black-jack style card game while either fatigued or reasonably alert. Findings showed that both fatigued and alert participants rated higher risk bets as more ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…The research presented in the present paper draws on and extends the work of Frings et al (2012), Parkin et al (2007) and Vansteenkiste et al, (2013) that with a cycle lane it is also the case that motor traffic may pass closer to a cycle user than they would if the cycle user and the motor vehicle driver were sharing the same lane (Parkin and Meyers, 2010). No evidence has shown directly that cycle lane presence reduces the perceived risk of cycling.…”
Section: Attention Allocationsupporting
confidence: 51%
See 1 more Smart Citation
“…The research presented in the present paper draws on and extends the work of Frings et al (2012), Parkin et al (2007) and Vansteenkiste et al, (2013) that with a cycle lane it is also the case that motor traffic may pass closer to a cycle user than they would if the cycle user and the motor vehicle driver were sharing the same lane (Parkin and Meyers, 2010). No evidence has shown directly that cycle lane presence reduces the perceived risk of cycling.…”
Section: Attention Allocationsupporting
confidence: 51%
“…It is possible that attention influences risk perception which influences behavioural choice. This model is based on a well-established assumption that risk perception guides subsequent behaviour (see Frings, 2012, for an example).…”
Section: Risk Attention and Behavioural Choicementioning
confidence: 99%
“…It appears that not only does alcohol consumption make tasks more difficult, associated expectancies also increases dyad members' confidence in avoiding negative outcomes (or achieving positive ones). This, in turn, is likely to lead to lowered risk perception and higher risk tolerance (see Frings, ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may contrast previous research examining a similar question. Frings ( 2012 )examined the effect of experimentally attenuated sleep duration (< 5 hours), over the course of two nights, on decision-making. Frings found that individuals who had experimentally reduced sleep duration bet significantly more on a probabilistic decision-making task compared to those whose sleep patterns were not manipulated.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that after 24 hours of continual wakefulness neural processing patterns while performing a gambling task significantly change in a manner that may suggest a propensity towards increased risk seeking ( Venkatraman, Chuah, Huettel & Chee, 2007 ). In addition, fatigue (measured using the Piper Fatigue Scale)appears to have a significant positive correlation with the amount of risk taken in a decision-making task (defined as amount of money bet during a gambling task)( Frings, 2012 ). Considered together, these studies suggest that prolonged and continual wakefulness, fatigue, or accumulated sleep debt may increase risky decision-making in individuals who gamble.…”
Section: Introductionmentioning
confidence: 99%